2022
DOI: 10.1038/s41598-022-08882-x
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein cut-off for early tocilizumab and dexamethasone prescription in hospitalized patients with COVID-19

Abstract: Dexamethasone and tocilizumab have been associated with reduction in mortality, however, the beneficial effect is not for all patients and the impact on viral replication is not well defined. We hypostatized that C-reactive protein (CRP) could help in the identification of patients requiring anti-inflammatory therapy. Patients admitted for > 48 h in our hospital for a confirmed or suspected infection by SARS-CoV-2 from February 2020 to February 2021 were retrospectively evaluated. The primary outcome was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…CRP, sIL-2R, and ferritin levels in both groups and D-dimer levels in TCZ (+) patients were aberrant values. CRP levels in TCZ (+) patients were more than 3.5 mg/dL, which is its cut-off for the beneficial effects of TCZ treatment [ 37 ]. The respiratory functions in TCZ (+) patients were significantly exacerbated compared to those in TCZ (−) according to their S/F ratio.…”
Section: Resultsmentioning
confidence: 99%
“…CRP, sIL-2R, and ferritin levels in both groups and D-dimer levels in TCZ (+) patients were aberrant values. CRP levels in TCZ (+) patients were more than 3.5 mg/dL, which is its cut-off for the beneficial effects of TCZ treatment [ 37 ]. The respiratory functions in TCZ (+) patients were significantly exacerbated compared to those in TCZ (−) according to their S/F ratio.…”
Section: Resultsmentioning
confidence: 99%
“…A potential limitation of IP-10 as a clinical tool is that it is not available for routine determination in most laboratories, even when it is not a complex or expensive procedure, and that interpretation and quantification are not standardized. For this reason, the role of commonly used inflammatory markers such as CRP has been assessed in previous studies [ 7 , 10 ], which have shown a correlation of high CRP levels with clinical evolution. In our study, although a good correlation of CRP with IP-10 levels was observed, we were unable to identify a cutoff value for CRP or other commonly used serum or cellular markers, with a good predictive yield.…”
Section: Discussionmentioning
confidence: 99%
“…Some serum markers have been evaluated as specific indicators of disease progression, including inflammatory and coagulation markers (such as C-reactive protein [CRP], ferritin, and D-dimer [DD]) and inflammatory cytokines (such as IL-6, IL-2R, IL-10, monocyte chemoattractant protein [MCP]-1 or tumor necrosis factor–α). Previous studies have suggested that CRP [ 6 , 7 ] and IL-6 [ 8 , 9 ] levels in earlier stages of COVID-19 predict clinical evolution and could be used for the selection of candidates for immunomodulatory therapy [ 7 , 10 ]. In fact, clinical trials with anti-IL-6, in which selected patients had elevated biomarkers, have shown benefit.…”
mentioning
confidence: 99%
“… 8 12 Various studies have demonstrated that the determination of hyperinflammation and its degree may have a pivotal role in order to predict prognosis and decide on immunomodulatory therapy early in the intensive care unit (ICU). 7 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Various studies have demonstrated that the determination of hyperinflammation and its degree may have a pivotal role in order to predict prognosis and decide on immunomodulatory therapy early in the intensive care unit (ICU). 7,13,14 Despite hyperinflammation is a well-known and important condition in COVID-19, few criteria and scoring systems to detect hyperinflammation have been evaluated. 5,15,16 A recent study by Webb et al 5 proposed to determine specific criteria for COVID-19 associated hyperinflammation syndrome (cHIS).…”
Section: Introductionmentioning
confidence: 99%